2017
DOI: 10.2116/xraystruct.33.11
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of (2-Picolinato)bis(2,2′-bipyridine)ruthenium(II) Chloride

Abstract: 11The coordination chemistry of ruthenium(II) complexes with polypyridyl ligands has been an area of great interest, because of their redox properties and photochemistry. 1 We reported on the syntheses, crystal structures, and isomerization reactions of the ruthenium(II) complexes bearing a di-2-pyridyl ketone (dpk); trans(Cl),cis(S)-[RuCl2(dpk-κ 2 N,O)(dmso-S)2] and cis(Cl),cis(S)-[RuCl2(dpk-κ2 The crystal structure of the trans(Cl),cis(S)-isomer revealed that the oxygen of the ketone group on the dpk ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…There are only two entries containing [Ru II (bipy) 2 (pic)] + , but with different simple counterions, such as Cl − and PF 6 − . 21,30 Also, only four structures with the same [cis-Ru III Cl 2 (pic) 2 ] − anion were found in the CSD database. 12,13 The following analyses were performed to check the homogeneity and purity of the bulk material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are only two entries containing [Ru II (bipy) 2 (pic)] + , but with different simple counterions, such as Cl − and PF 6 − . 21,30 Also, only four structures with the same [cis-Ru III Cl 2 (pic) 2 ] − anion were found in the CSD database. 12,13 The following analyses were performed to check the homogeneity and purity of the bulk material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A search in the CSD database revealed that no similar mixed-valence Ru­(II)/Ru­(III) ion-pair complex of the structure described here could be found. There are only two entries containing [Ru II (bipy) 2 (pic)] + , but with different simple counterions, such as Cl – and PF 6 – . , Also, only four structures with the same [ cis -Ru III Cl 2 (pic) 2 ] − anion were found in the CSD database. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations